Sport-related performance anxiety : associations between performance anxiety and sport participation in adolescent dual career athletes in Iceland - Harpa Hrund Einarsdóttir 1997- (2021)
Organized sports demonstrate a more positive influence on youths’ well-being than any other type of physical activity. With increasing age and competence, the sports environment may change and become more demanding of an athlete’s ability resulting in a level of anxiety that can debilitate athletic performance. The objective of the study was to examine sport-related performance anxiety in dual career athletes in an upper secondary school in Iceland and potential differences by type of sport, genders, and parental support. A sample of 77 athletes (64 males and 13 females) aged between 16 and 19 years participated in the study, representing both individual and team sports. A self-report questionnaire including the Sport Anxiety Scale-2 (SAS-2) was used to assess three distinct aspects of anxiety (somatic anxiety, worry, and concentration disruption). Athletes in individual sports reported higher levels of sport anxiety than athletes in team sports based on the scores of SAS-2. No differences in sport anxiety were found between genders. In addition, correlation between scores of sport anxiety and parental support was non-significant. The findings suggest that anxiety differs in athletes depending on their type of sport. Keywords: sport anxiety, performance, type of sport, gender, parental support Skipulögð íþróttastarfsemi hefur sýnt jákvæðari áhrif á ungmenni en nokkur önnur líkamleg hreyfing. Með hækkandi aldri og aukinni getu, hefur íþróttaumhverfið tilhneigingu til að reynast kröfuharðara á frammistöðu íþróttafólks. Afleiðingar þess geta aukið kvíða íþróttafólks og hamlað frammistöðu. Markmið rannsóknarinnar var að kanna íþróttatengdan frammistöðukvíða meðal nema á afrekssviði í framhaldsskóla á Íslandi og hvort munur væri til staðar milli tegund íþróttar, kynja og stuðnings foreldra. Úrtakið samanstóð af 77 íþróttaiðkendum (64 körlum og 13 konum) á aldrinum 16 til 19 ára, bæði einstaklings- og liðsíþróttafólki. Sjálfsmatskvarði sem innihélt meðal annars Sport Anxiety Scale-2 (SAS-2) var notaður til að meta ...